Construction of the Energy Band Diagram of Hydrogen Terminated Diamond and Silicon Nanowires. Issue 12 (23rd November 2017) - Challinger, Susanna; Baikie, Iain; Birdwell, A. Glen; Strehle, Steffen
Abstract : We demonstrate the use of a combined ambient pressure and UHV photoemission system for absolute work function characterization. We describe measurements of the valence band position of Hydrogen Terminated Synthetic Diamond (HTSD) under different pressures. The diamond exhibits a nanoscale surface conductivity with a 2D hole gas of ≈10 nm depth. The same system also allows contact potential difference Kelvin probe measurements for determination of relative Fermi level position from 1 to 1.1 × 10 −11 Bar. Combined with UV‐Surface Photovoltage determination of the band gap, this allows a complete reconstruction of the surface energy band diagram of this material. The valence band edge was found to be 4.9 eV under ambient conditions and 4.4 eV under UHV, relative to the vacuum level. The ambient pressure photoemission technique was also used to reconstruct the energy band diagram of bottom‐up grown silicon nanowires. They had a valence band maximum at 5.04 ± 0.05 eV. Both the HTSD and silicon nanowires had high photoemission yield characteristics which suggests that these materials could be used as an electron source. This illustrates the suitability of photoemission and Kelvin probe techniques for investigating the macroscopic work function characteristics of surfaces with nanostructures and nanoscale surface conductivity. Abstract : We demonstrate a novel UHV to ambient pressure, photoemission and Kelvin probe system, for energy level characterisation of hydrogen terminated diamond and silicon nanowire surfaces. We compare photoemission measurements of hydrogen terminated diamond under different conditions, illustrating the suitability of these techniques for investigating the macroscopic work function characteristics of surfaces.